ChemInform Abstract: Imidazole and Imidazoline Derivatives as N‐Donor Ligands for Nickel‐Catalyzed Kumada‐Tamao‐Corriu Coupling. Issue 18 (11th April 2013) - Iwamoto, Ryo; Hayashi, Masahiko
Abstract The reaction can be applied to the aromatic bromides, iodides and triflates to afford the coupling products (III) along with the homo‐coupling biaryls (IV).